Changes in the secretory functions of the thyroid gland during pregnancy. - Krzysztof Mariusz Halczuk; Bolesław Karwowski (Polish Pharmaceutical Society, 2021)
Thyroid - the odd endocrine gland regulates the metabolism of fats, carbohydrates and proteins, among other things. It is not a vital organ. However, the level of thyroid hormones has a significant impact on human development, especially in the period of fetal and neonatal life. It should be noted that the secretory activity of the mother's thyroid gland is the only source of thyroid hormones: thyroxine and triiodothyronine in the early stages of its development. In addition, the body of a pregnant woman adjusts the secretion and circulation of these hormones in the blood so that they provide optimal conditions for the prenatal development of the child - in particular the development of the nervous system. Physiological changes caused by pregnancy are intense and have a significant impact on the health of the future mother and the fetus, which is particularly important in the case of women who had thyroid disorders before pregnancy. Chorionic gonadotropin secreted by the placenta, acting as a thyrotropic, directly changes the secretory functions of the thyroid gland. Changes in the amino acid balance of a pregnant woman affect concentration of thyroid hormones in the blood. Moreover, the phenomenon of pregnancy immunosuppression may temporarily reduce the symptoms of thyroid diseases. Hypothyroidism and hyperthyroidism diagnosed in pregnant women has a negative impact on the course of pregnancy because it increases the risk of miscarriage and fetal death. If the mother's thyroid disease is left untreated, the health of the fetus is also at risk - the child's neurological development and cognitive function may be impaired later in life. For this reason, the diagnosis of thyroid diseases in pregnant women is a diagnostic standard. In the presented article, on the basis of the available literature, the general physiology of the thyroid gland has been discussed, with particular attention being paid to changes related to its secretory function during pregnancy. These changes were compared with the reference values determined for the model of a healthy person (adults).